Everyday Deeds: Enactive Protest, Exit, and Silence in Deliberative Systems. (October 2017) - Rollo, Toby
The deliberative systems approach is a recent innovation within the tradition of deliberative democratic theory. It signals an important shift in focus from the political legitimacy produced within isolated and formal sites of deliberation (e.g., Parliament or deliberative mini-publics), to the legitimacy produced by a number of diverse interconnected sites. In this respect, the deliberative systems (DS) approach is better equipped to identify and address defects arising from the systemic influences of power and coercion. In this article, I examine one of the least explored and least understood defects: the exclusion of non-speaking political actors generated by the uniform privileging of speech in all sites within a system. Using the examples of prefigurative protest, Indigenous refusal to deliberate, and the non-deliberative agency of disabled citizens, I argue that the DS approach allows theorists to better understand forms of domination related to the imposition of speech on those who are either unwilling or unable to speak.